Front Cover Picture: B(C6F5)3‐Catalyzed Deoxygenative Reduction of Amides to Amines with Ammonia Borane (Adv. Synth. Catal. 10/2019). Issue 10 (25th February 2019) - Pan, Yixiao; Luo, Zhenli; Han, Jiahong; Xu, Xin; Chen, Changjun; Zhao, Haoqiang; Xu, Lijin; Fan, Qinghua; Xiao, Jianliang
Abstract : The front cover picture, provided by Lijin Xu and co‐workers, illustrates the first B(C6 F5 )3 ‐catalyzed reduction of amides into the corresponding amines with readily accessible and stable ammonia borane under mild reaction conditions. The role of BF3 ⋅OEt2 co‐catalyst is to activate the amide carbonyl group via the in situ formation of an amide‐boron adduct. This metal‐free protocol provides facile access to various amines in good to excellent yields with high functional group tolerance. Details of this work can be found in the full paper on pages 2301–2308 (Y. Pan, Z. Luo, J. Han, X. Xu, C. Chen, H. Zhao, L. Xu, Q. Fan, J. Xiao, Adv. Synth. Catal . 2019, 361, 2301–2308; DOI: 10.1002/adsc.201801447 ).